Kaleidoscopic Odessa : history and place in contemporary Ukraine - Richardson, Tanya (Toronto : University of Toronto Press, 2008)
"Ukraine's 'Orange Revolution' and its aftermath exposed some of the deep political, social, and cultural rifts running through the former Soviet republic. This book explores the intersection of these divisions in Odessa, a Black Sea port in Ukraine that was once the Russian Empire's southern window to Europe. Odessans view their city as a cosmopolitan place with close ties to Russia and the world despite the state's attempt to generate feelings of national belonging. Odessans' sense of place is cultivated in various urban spaces through the narration of histories that are both intimate and official, imperial and local, traumatic and nostalgic. In illuminating the interplay of history with competing senses of place and nation in Odessa, this study shows how nation-building policies interact with the legacies and memories of the Russian Empire and the Soviet Union."--Jacket.
1. Kaleidoscopic Odessa -- 2. Uncertain Subjects: Youth, History, and Nation -- 3. Living History and the Afterlives of States -- 4. On Odessa's Kolorit and the Place(s) of Moldovanka -- 5. Walking Streets, Talking History: The Making of Odessa -- 6. Between Cosmopolitan and Provincial: Spaces of History and the Place of Odes(s)a.
Includes bibliographical references (pages 241-262) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Description based upon online resource; title from PDF title page (viewed July 21, 2021).
JSTOR
Keywords: Odesa (Ukraine) -- History; Odesa (Ukraine) -- Social conditions; Ethnology -- Ukraine -- Odesa; Sociology, Urban -- Ukraine -- Odesa; Odesa (Ukraine) -- Biography; Odessa (Ukraine) -- Histoire; Odessa (Ukraine) -- Conditions sociales; Odessa (Ukraine) -- Biographies; Ethnologie -- Ukraine -- Odessa; Sociologie urbaine -- Ukraine -- Odessa; 15.70 history of Europe; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; SOCIAL SCIENCE -- Anthropology -- General; Social conditions; Sociology, Urban; Ukraine -- Odesa; Kollektives Gedächtnis; Odessa; Odesa; Geschichte; Ethnology -- Ukraine -- Odesa; Geschichte; Odesa (Ukraine) -- History; Odesa (Ukraine) -- Social conditions; Biographies; History